Antibiotic prescription in bone augmentation and dental implant procedures: a multi-center study - Nikoo Bazsefidpay; Fredrik Holmqvist; Dalia Khalil; Cecilia Larsson Wexell; Margareta Hultin; Peter Nilsson; Bodil Lund (BMC, 2023)
Abstract Background Adherence to antibiotic recommendations and safety aspects of restrictive use are important components when combating antibiotic resistance. The primary aim of this study was to assess the impact of national guidelines on antibiotic prescriptions for bone augmentation procedures among dentists working at three specialized clinics. The secondary aim was to assess the occurrence of postoperative infections. Methods Medical charts of 400 patients treated with bone augmentation were reviewed: 200 in the years 2010-2011 and 200 in 2014-2015. The Swedish national recommendations for antibiotic prophylaxis were published in 2012. Results There was a wide variation in antibiotic regiments prescribed throughout the study. The number of patients treated with antibiotic prophylaxis in a single dose of 2 g amoxicillin, and treated as advocated in the national recommendations, was low and decreasing between the two time periods from 25% (n = 50/200) in 2010-2011 to 18.5% (n = 37/200) in 2014-2015. The number of patients not given any antibiotics either as a prophylactic single dose or during the postoperative phase increased (P < 0.001). The administration of a 3-7-days antibiotic prescription increased significantly from 25.5% in 2010-2011 to 35% in 2014-2015. The postoperative infection rates (4.5% and 6.5%) were without difference between the studied periods. Smoking and omitted antibiotic prophylaxis significantly increased the risk of postoperative infection. Logistic regression analyses showed that patient male gender and suffering from a disease were predictive factors for the clinician to adhere to the guidelines. Conclusions After introduction of national recommendations for antibiotic prophylaxis before bone augmentation procedures, the patient group receiving a single preoperative dose decreased while the group not given antibiotic prophylaxis increased. There was no difference in occurrence of postoperative infections between the two time periods. The results indicate a need for educational efforts and strategies for implementation of antibiotic prudence and awareness among surgeons performing bone augmentation procedures.